Metastatic melanoma patients' sensitivity to ipilimumab cannot be predicted by tumor characteristics. Issue 9 (October 2017) - Rossfeld, Kara; Hade, Erinn M.; Gangi, Alexandra; Perez, Matthew; Kinsey, Emily N.; Grabska, Joanna; Ederle, Ashley; Zager, Jonathan; Salama, April K.; Olencki, Thomas E; Beasley, Georgia M
Abstract : Background: Immune checkpoint inhibitors have dramatically changed the prognosis for patients with metastatic melanoma. However, not all patients respond to therapy and toxicities can be severe leaving need for reliable clinical predictive markers. Methods: We examined primary tumor characteristics including ulceration, BRAF mutation status, and Breslow depth in patients who subsequently developed stage IV disease and were treated with ipilimumab at 3 institutions. Patients in this study were not treated on clinical trials. To investigate the relationship between patient characteristics at the time of diagnosis and survival following melanoma diagnosis we utilized Cox proportional hazards models, accounting for delayed entry into the study cohort. Cox models estimate the age and institution adjusted hazard ratios for risk of death. Results: Of patients (n=385) treated with ipilimumab for stage IV melanoma, 302 met inclusion criteria. The complete response to ipilimumab was 5%, partial response was 13%, 18% had stable disease, 62% had progressive disease, and 5 unknown. The median overall survival rate was 2.03 years [95% confidence interval (CI): 0.13, 3.05]. Primary tumor Breslow depth, lymphovascular invasion, BRAF status, and ulceration did not predict sensitivity to ipilimumab. In this study patient cohort, BRAF mutation (adjusted hazard ratio: 1.43, 95% CI: 0.98, 2.07) and presence of ulceration (adjusted hazard ratio: 1.47, 95% CI: 0.95, 2.26) contributed to an increased risk of death. Conclusions: The presence of ulceration did not correlate with sensitivity to ipilimumab. Ulceration of the primary tumor and a BRAF mutation were moderately associated with worse survival in patients with metastatic melanoma treated with ipilimumab.